Mathematical Taxonomy of Health Insurance Models: Conventional Approaches and the Emergent C&C Paradigm - David Mark Dror (ZBW - Leibniz Information Centre for Economics, 2025)
This paper introduces a formal mathematical taxonomy of four principal health insurance models: Bismarckian, Beveridgean, Commercial, and Collaborative & Contributive (C&C). Each model is analyzed for its structural characteristics, sustainability conditions, and demographic resilience under stress. Unique to the C&C model is the incorporation of trust as a variable affecting sustainability and participation. By comparing the equilibrium and value functions across models, the paper reveals fundamental differences in their capacity to withstand demographic and financial pressures. The proposed taxonomy enhances both theoretical understanding and practical evaluation of global health insurance systems. – – Gesundheitssysteme weltweit stehen vor wachsenden Herausforderungen in Bezug auf ihre Nachhaltigkeit. Dieser Beitrag bietet eine mathematisch fundierte Analyse von vier zentralen Modellen: Bismarck-Modell, Beveridge-Modell, kommerzielle Versicherung und das kollaborative & beitragsbasierte (C&C) Modell. Es werden formale Strukturen, Gleichgewichtsbedingungen und Resilienzmetriken dargestellt, wobei das C&C-Modell durch die explizite Einbindung von Vertrauen als besonders widerstandsfähig identifiziert wird.
Keywords: I13; 330; Mathematical taxonomy; Healthcare financing; Health insurance models; Mathematical modeling; Demographic resilience; System equilibrium; Risk pooling; Sustainability thresholds; Bismarckian system; Beveridgean system; Commercial insurance; Collaborative and Contributive (C&C) model; Trust dynamics